Anilinoquinazoline inhibitors of the RET kinase domain—Elaboration of the 7-position. Issue 11 (1st June 2016) - Jordan, Allan M.; Begum, Habiba; Fairweather, Emma; Fritzl, Samantha; Goldberg, Kristin; Hopkins, Gemma V.; Hamilton, Niall M.; Lyons, Amanda J.; March, H. Nikki; Newton, Rebecca; Small, Helen F.; Vishwanath, Swamy; et al.
Graphical abstract: Abstract: We have previously reported a series of anilinoquinazoline derivatives as potent and selective biochemical inhibitors of the RET kinase domain. However, these derivatives displayed diminished cellular potency. Herein we describe further optimisation of the series through modification of their physicochemical properties, delivering improvements in cell potency. However, whilst cellular selectivity against key targets could be maintained, combining cell potency and acceptable pharmacokinetics proved challenging.